Medicinske gobe: od zgodovinskih pripravkov do sodobne znanosti - Radić, Nataša (Medicinski razgledi, 2011)
In the past medicinal mushrooms have been widely used in Asia, but over the past several years dietary supplements con taining medicinal mushrooms have also been introduced on the pharmaceutical and food market of Europe and the United States of America in the total value of almost USD 4 billion in 2009. Pharmacologically, the most important group of active substances from almost all species of Bacidiomycetesmus hrooms are-glucan poly saccharides, which exhibit immunomodula tory and anti cancer activity. Some substances have additional antibacterial, antiviral and hepa to protective action. Protective antioxidant activity of medicinal mushrooms was also discovered and some of them may play an important role in the therapy of diabetes type II.
Keywords: therapy; zdravljenje; medicinske gobe; ß-glukani; klinične študije; imunomodulatorji; protitumorno delovanje